The emotion regulation training to improve quality of life in patients with hypertension - Kartika Mustafa; H.Fuad Nashori; Yulianti Dwi Astuti (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2016)
Background : Quality of life is an indicator of health. Quality of life is used to evaluate the physical and psychosocial effects of an illness suffered by a person, including a person’s knowledge and perception of the illness. In order to achieve optimal quality of life, patients with hypertension were reported frequent use defense mechanisms to repress emotions or regulate emotions. Objective : The aim of this study was to investigate the effect of emotion regulation training to improve the quality of life among patients with hypertension. The hypothesis of this study stated that there was an influence of emotion regulation training to quality of life among patients with hypertension. Methods : The quality of life was measured by using quality of life scale based on aspect from WHOQOL-BREF (1998). An experimental method used was a pre and post-test control group design. Data were analysed by using Mann Whitney U. Results : The researchers found that there was no difference in the level of quality of life between the experimental group and the control group were not given training. However, the results of this study indicate that the quality of life scores in the experimental group increased during follow-up (p=0,002 (p<0,05). This suggest that quality of life among experimental group has increased compared to the control group, and consequently it accepted the hypothesis. Conclusion : Emotion regulation strategies can helped a person to cope the life stress that can be associated with psychological distress and quality of life.